Identification and characterization of leprosy T cell antigens in the context of early diagnosis and CD1a restricted T cell activation - Kim, Hee Jin, author; Brennan, Patrick J., advisor; Schenkel, Alan R., committee member; Reist, Noreen E., committee member; Vissa, Varalakshmi D., committee member (Colorado State University. Libraries, 2011)
To view the abstract, please see the full text of the document.
Keywords: mycobacteria; lipoprotein; T cell; CD1a; leprosy